Implementasi Procedural Generation untuk Membangun Level Tactical RPG dengan menggunakan Metode Occupancy Regulated Extension - Anindita Setyamurti; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tactical RPG is a game where player controlling some unit tactically to complete goals in the level.There many game with this kind of genre, unfortunately only a few of them used Procedural Content Geneator (PCG) to generate content procedurally which used to increase replayability value and indirectly increase game lifespan. PCG on Tactical RPG games can be used to generate level, quest even a character. Level generation can be done using Occupancy Regulated Extension (ORE) method which putting some chunk together to create a complete level which can be measured how good the generated level using linearity expressiveness range. According to test, 93% of all generated level having high marginal values. In short, generating level using occupancy regulated extension will be resulted in pretty good level.